Leadership and Employee Loyalty in Nepalese Commercial Banks (The International Research Journal of Management Science, 2025)
Purpose- This study aims to examine the relationship between leadership styles and employee loyalty in Nepalese commercial banks, emphasizing the strategic importance of human capital for organizational sustainability. It explores how different leadership behaviors influence employees’ commitment and long-term attachment to their organizations.Design/Methodology/Approach-A quantitative research design was used to investigate the impact of leadership styles on employee loyalty. Data were collected through structured questionnaires from a purposive sample of 210 employees working in various functional roles and hierarchical levels across five leading commercial banks of Kathmandu Valley. Statistical analysis was conducted to examine the relationship between different leadership styles and employee loyalty.Findings-Results indicate that transformational leadership significantly enhances employee loyalty. Leaders who articulate a shared vision, encourage innovation, and provide individualized support foster stronger emotional bonds and commitment. Additionally, ethical and fair leadership behaviors, emphasizing employee well-being, also play a crucial role in promoting loyalty and retention.Implications-The study offers practical and valuable insights for human resource professionals and bank executives to design effective leadership development programs that emphasize transformational and ethical leadership. Such initiatives can foster employee engagement, reduce turnover, and promote workforce stability within the highly competitive banking environment of Nepal.Originality/Value-This study contributes to the limited empirical literature on leadership and employee loyalty in the Nepalese banking sector. It provides evidence-based insights on how specific leadership behaviors can influence employee attitudes to emerging economies.